2010
DOI: 10.1002/bdra.20713
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal choline supplementation mitigates behavioral alterations associated with prenatal alcohol exposure in rats

Abstract: BACKGROUND Prenatal alcohol exposure can alter physical and behavioral development, leading to a range of fetal alcohol spectrum disorders (FASD). Despite warning labels, pregnant women continue to drink alcohol, creating a need to identify effective interventions to reduce the severity of alcohol’s teratogenic effects. Choline is an essential nutrient that influences brain and behavioral development. Recent studies indicate that choline supplementation can reduce the teratogenic effects of developmental alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(164 citation statements)
references
References 131 publications
(150 reference statements)
5
154
2
1
Order By: Relevance
“…An examination of the groups separately revealed that small effect sizes and sample sizes would have to have been inordinately large to confidently draw conclusions from the results; in addition, the possibility of a type II error could not be ruled out (achieved power ranged from 0.13 to 0.84). The null findings of this clinical trial were unanticipated because of the strong evidence that has suggested beneficial effects of choline supplementation in animal models of both typical development (39) and prenatal alcohol exposure (3)(4)(5)(6)(7)(8)10). However, this investigation was only one of a few trials to translate the aforementioned animal research to a human clinical trial of choline supplementation in FASDs, and previous studies, at earlier ages, have suggested some positive beneficial effects (13,14).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…An examination of the groups separately revealed that small effect sizes and sample sizes would have to have been inordinately large to confidently draw conclusions from the results; in addition, the possibility of a type II error could not be ruled out (achieved power ranged from 0.13 to 0.84). The null findings of this clinical trial were unanticipated because of the strong evidence that has suggested beneficial effects of choline supplementation in animal models of both typical development (39) and prenatal alcohol exposure (3)(4)(5)(6)(7)(8)10). However, this investigation was only one of a few trials to translate the aforementioned animal research to a human clinical trial of choline supplementation in FASDs, and previous studies, at earlier ages, have suggested some positive beneficial effects (13,14).…”
Section: Discussionmentioning
confidence: 88%
“…Notably, our group was the first, to our knowledge, to examine the effects of a nutritional intervention of choline with the use of a rodent model of FASDs (3). Through a series of studies, we showed that choline reduces the severity of alcohol's adverse effects on behavioral development whether administered perinatally (4,5) or postnatally after alcohol exposure has occurred (3,6,7). Choline mitigates behavioral deficits on tasks that depend on the functional integrity of the hippocampus and prefrontal cortex including spatial learning and memory (8), hyperactivity (8), trace classical conditioning (9,10), and working memory (3).…”
Section: Introductionmentioning
confidence: 99%
“…Increased miR-467b-5p in Slc17a6 promoter resulting in hypomethylation of hippocampal H3K4me3 at the Slc17a6 promoter, with corresponding increased mRNA levels of hippocampal Slc17a6, although its protein product VGLUT2 was decreased Rat Maternal ethanol exposure during pregnancy [110,112,114,128,[268][269][270][271] Behavioral, learning and memory deficits, and decreased birth and brain weights, and incisor emergence [284] Hypomethylation of the sperm LINE-1 gene Human/ cohort study Maternal exposure to organophosphate pesticides and persistent organic pollutants [291] Decreased adiponectin levels with increasing levels of cord blood p,p′-dichlorodiphenyl dichloroethene (DDE) in female offsprings…”
Section: Hypomethylation Of the Pancreatic Il13ra2 Genementioning
confidence: 99%
“…) [110,112,114,128] Choline supplementation enhanced offsprings' ethanol induced learning and memory deficits…”
Section: Hypomethylation Of the Pancreatic Il13ra2 Genementioning
confidence: 99%
See 1 more Smart Citation